2004
DOI: 10.1183/09031936.04.00109704
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of MRSA pneumonia by oral vancomycin decontamination: a randomised trial

Abstract: This study was undertaken to assess whether oropharyngeal vancomycin may control oropharyngeal carriage and lower airway infection due to methicillinresistant Staphylococcus aureus (MRSA) acquired in the intensive care unit (ICU). Secondary endpoints were the emergence of vancomycin-resistant enterococci, vancomycin-intermediate S. aureus and vancomycin consumption.A total of 84 patients, admitted to a medical/surgical ICU and mechanically ventilated for w72 h, were randomly assigned to control (n=42) or test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 34 publications
(36 reference statements)
2
39
0
1
Order By: Relevance
“…More novel treatment modalities for intestinal MRSA elimination to control transmission or subsequent infections, e.g., using oral vancomycin, have been described merely in uncontrolled or observational studies. Oral vancomycin treatment results were reported that showed that the eradication of MRSA intestinal carriage by enteral vancomycin in subsets of adult ICU patients [58][59][60] as well as in pediatric patients [61,62] was effective, but had limited effect on the prevention of transmission. The results from prospective controlled studies of intestinal MRSA decolonization are urgently awaited.…”
Section: Eradication Of Intestinal Carriagementioning
confidence: 99%
“…More novel treatment modalities for intestinal MRSA elimination to control transmission or subsequent infections, e.g., using oral vancomycin, have been described merely in uncontrolled or observational studies. Oral vancomycin treatment results were reported that showed that the eradication of MRSA intestinal carriage by enteral vancomycin in subsets of adult ICU patients [58][59][60] as well as in pediatric patients [61,62] was effective, but had limited effect on the prevention of transmission. The results from prospective controlled studies of intestinal MRSA decolonization are urgently awaited.…”
Section: Eradication Of Intestinal Carriagementioning
confidence: 99%
“…A recent study from Spain comparing MRSA rates in burns patients receiving SDD without vancomycin for a 5-year period to rates in a subsequent 4-year period when vancomycin was added to the SDD regimen demonstrated a significant reduction in MRSA acquisition in the latter period [19]. Other studies have demonstrated a reduction in MRSA acquisition [20,21] and control of an MRSA outbreak [22] with vancomycin-containing regimens. No significant problems with the emergence of VRE were noted in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…e) Oral Hygiene Oropharyngeal colonization is of significant importance in the pathogenesis of Ventilator associated pneumonia, and a targeted approach to prevent colonization at this site may be an effective method of infection prevention. Several studies have documented benefit of selective oral decontamination in adults [17][18][19]. Surveys performed in the US and UK suggested that oral care methods were not consistent with current research and oral care protocols [20,21].…”
Section: Monitoringmentioning
confidence: 97%